The Role of E-Module in the Teaching and Learning Process in Vocational Secondary Schools (SMK): a Literature Review - Agustian, Dendi; Wardoyo, Siswo; Amartha, Amelda; Anjani, Triska Adelia; Wulansari, Tari; Marsanda, Elisa (Al Hikmah: Journal of Education, 2024)
The implementation of e-modules in learning at Vocational High Schools (SMK) has become an innovative solution relevant to technological advancements and the demands of Industry 4.0. This article aims to explore the role of e-modules in improving student learning outcomes at SMKs, as well as the challenges and opportunities of their implementation. The methodology used in this research is a systematic literature review, with criteria for selecting relevant articles based on the themes of e-module-based learning, vocational education, and the application of technology in education. The selected articles were analyzed using a content analysis approach to identify trends, benefits, challenges, and outcomes obtained from the implementation of e-modules in SMKs. This research also examines the implementation of Project-Based Learning (PjBL) and Problem-Based Learning (PBL) approaches in the context of e-modules, which have been shown to enhance student engagement and the mastery of practical competencies required in the workforce. However, challenges such as limited technological infrastructure and teachers' readiness in developing high-quality e-modules still need to be addressed. The analysis results indicate that e-modules can improve the quality of learning at SMKs, but specific strategies are needed to overcome existing barriers to optimize their use.